Cultural Heritage Tourism in Bhaktapur - Kafle, Dol Raj (HISAN: Journal of History Association of Nepal, 2025)
This study explores how Bhaktapur has preserved and promoted its cultural heritage while adapting to modern life. It also examines how these efforts support long-term cultural tourism. It focuses on both tangible and intangible aspects of culture, including buildings, festivals, traditional crafts, etc. Special attention is given to the role of the local community and tourism in this process. The research paper employs a qualitative approach, incorporating field visits, the examination of historical records, and a review of relevant books, articles, and government reports. It also includes direct observation and talks with local artisans. The findings show that Bhaktapur’s success in heritage preservation is mainly due to strong local leadership. Important efforts include training programs for traditional craftsmen and the opening of technical schools. As a UNESCO World Heritage Site, Bhaktapur remains rich in Newar traditions and festivals like Bisket Jatra, Navadurga Jatra, Gai Jatra, Indra Jatra, etc. Despite the growth of tourism, the city has largely preserved its historic buildings and cultural practices. Bhaktapur, a beautiful cultural city, is a good example of how heritage can be managed well. Its approach helps protect cultural identity, supports tourism, and benefits the local economy. This case may serve as a guide for other historic cities with rich cultural heritage.